Relationship between Perceived Parenting Styles and Personal Growth Initiative among Adolescents - Batool, Sumbal Batool; Khurshid, Mona (PJE, 2024)
The current study investigates the relationship between perceived parenting styles and adolescent’s personal growth initiative. Data was collected from Rawalpindi and Islamabad. Participant’s age range was from 12 to 18 with both male (n = 116) and female (n = 184). Short Form of Egna Minnen Betriafenda Upfostron (EMBU) Urdu- version (Mazhar, 2020) and Personal Growth Initiative Scale - II (PGI- II) Urdu- version translated by Sadia Zaman (2018) were used for assessment. Perceived parental warmth exhibited significant positive correlated with personal growth initiative. Perceived parental rejection showed negative correlated with personal growth initiative. Personal growth initiative is not a gender based. The joint family system facilitated the utilization of resources for adolescents' growth. Adolescents from government institutions perceived more parental rejection and over- protection. Middle born participants perceived more parental rejection. Last born perceived parental emotional warmth and more opportunities to utilize resources. Education was positively correlated with parental emotional warmth and negatively correlated with parental over- protection. Age was negatively correlated with the perception of parental rejection and over- protection.